Bolivia’s New Constitution: Towards Participatory Democracy and Political Pluralism? - Schilling-Vacaflor, Almut (European Review of Latin American and Caribbean Studies, 2011)
In Bolivia, rights to increased political participation and the recognition of indigenous political systems are interrelated. The new constitution of 2009 defines Bolivia as a representative, participatory and communitarian democracy. It incorporates enhanced mechanisms and institutions for participatory democracy. Moreover, new social rights have been anchored in the constitution and a plurinational state is supposed to be constructed. The article raises the question of whether the new constitution will change the relations between state and civil society considerably and whether a new democratic model is being established in Bolivia. The author argues that there are many limiting factors when it comes to putting the emancipatory elements of the constitution into practice. These include the increased strength of the executive branch, the intent of the government to co-opt civil society organizations and to exclude dissident views, the resistance of the conservative opposition to losing some of its privileges, the deep-rooted social inequality, the social conflicts and polarization, the resource dependence of the current economic model, and the authoritarian characteristics of indigenous selfgovernance structures. The article demonstrates that the new Bolivian constitution cannot create a new society but that the processes around the elaboration of a new basic law have contributed to considerable changes in the social, political and symbolic order.Resumen: La nueva Constitución de Bolivia: ¿Hacia la democracia participativa y el pluralismo político?En Bolivia, los derechos a una creciente participación política y el reconocimiento de los sistemas políticos indígenas están interrelacionados. La nueva Constitución de 2009 define a Bolivia como una democracia representativa, participativa y comunitaria. Incorpora mecanismos mejorados e instituciones para forjar una democracia participativa. Además, los nuevos derechos sociales han sido anclados en la Constitución y se supone que se debe construir un estado plurinacional. En el artículo se pregunta si la nueva Constitución cambiará de forma considerable las relaciones entre el estado y la sociedad civil o si se establece un nuevo modelo democrático en Bolivia. La autora argumenta que hay muchos factores limitantes cuando se trata de llevar a la práctica los elementos de emancipación de la Constitución. Entre estos se encuentran el fortalezimiento de la rama ejecutiva, el intento del gobierno de co-optar a organizaciones de la sociedad civil y de excluir las visiones disidentes, la resistencia de la oposición conservadora ante la pérdida de algunos de sus privilegios, la profundamente enraizada desigualdad social, los conflictos sociales y la polarización, la dependencia de los recursos naturales del actual modelo económico y las características autoritarias de las estructuras de autogobierno indígena. En el artículo se demuestra que la nueva Constitución boliviana no puede crear una nueva sociedad sino que son los procesos en torno a la elaboración de una nueva legislación básica, los que han contribuido a provocar importantes cambios en los ámbitos social, político y simbólico.